Classification and management of hypersensitivity reactions - Baik, Maryam Abdullah; Al Nihab, Ali Naji; Al Aman, Abdulmanem Mohammed; Ghareeb, Ameen Ridha Al; Alaish, Mohammed Hashim; Awani, Ashraf Hassan Al; Al-Jadher, Ahmed Mansour; Al Muaddi, Faisal Mohammed; Hussain Al-Shehab, Ali; Tufaif, Tayseer Ali Al; Alsheef, Hussain Ahmad (International Journal Of Community Medicine And Public Health, 2022)
An inappropriate or excessive immune response to an antigen that has unfavourable effects is referred as a hypersensitivity reaction. People who have experienced at least one prior exposure to the antigen are more likely to have the symptoms. Nearly 60 years ago, Gell and Coombs first classified hypersensitivity reactions into four broad categories. Many forms of hypersensitivity reactions frequently occur at the same time, especially in allergic disorders. The purpose of this research is to review the available information about the classification and management of hypersensitivity reactions. Allergen-specific immunoglobulin E, which is associated with the high-affinity receptors of basophils and mast cells mediates type 1 hypersensitivity reactions. These receptors are cross-linked by allergens, which release mediators that elicit urticaria, angioedema, and anaphylaxis. Immunoglobulin G and immunoglobulin M attach to self-antigens on cell surfaces in type II reactions, which can lead to phagocytosis, and cytotoxicity that is complement-directed and antibody-dependent all of which can lead to tissue damage. Immune complexes of immunoglobulin G and immunoglobulin M with antigens, which deposit in tissues and directly harm organs, mediate type III reactions. T cells mediate type IV reactions which are delayed responses. In every case of allergic hypersensitivity, the trigger must be stopped right away. Antihistamines, glucocorticoids, and epinephrine are used to treat acute responses Some potential management techniques include drug allergy testing, graded challenges, desensitization, and/or choosing an alternative, non-cross-reactive substance. Further clinical research is however needed for the elaborated study of hypersensitive reactions and development of preventive strategies.